Socio - Economic Profile of Samastipur District: Examining the Impact of Rural Road Connectivity on Socio-Economic Development (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The connectiveness of rural roads is a key component of rural growth as it promoted access to the economic and social facilities, thus creating greater agricultural production, non-farm jobs and non-agriculture production.